Positive thinking and its relation to the motivation of learning among the students of third year of secondary education in the Wilaya of Msila A field study in Ain Al - Hadjel high-schools - Mammeri , mahfoud (Journal of Social Sciences and Humanities, 2020)
The study aims to know the level of positive thinking and learning motivation for the study sample, as well as the study of the relationship between positive thinking and learning motivation of third-level students year of secondary education. It seeks to answer the following questions : -What is the level of positive thinking among third-year students in secondary education? -What is the level of motivation of third-year students learning in secondary education? - Is there a correlation between learning and the motivation of positive thinking among third-year students in secondary education? The use of the descriptive approach and the application of Dr. Ibrahim Abdul Sattar's positive thinking and the measurement of the motivation to learn of Dr. Ahmed Douka and after checking the psychometric properties of a sample of 40 students, a study of basis was carried out on a sample of 150 students. Hence the following results : -Third-year students in secondary education have an acceptable model of positive thinking - And a high average learning motivation. -There is a correlation between positive thinking and motivation of learning.